“PROCESO HISTORICO DEL MERCADO DE PRODUCTORES SAN PEDRO DE RIOBAMBA Y EL IMPACTO SOCIO-ECONOMICO EN LOS MORADORES DE LOS BARRIOS ALEDAÑOS EN LOS ULTIMOS 5 AÑOS” - Cáceres Carrillo, Oswaldo Fabián (2014)
This thesis shows the impacts on marketing at the wholesale level in the city of Riobamba after the creation and operationalization of the Municipal Farmers Market San Pedro de Riobamba - EMMPA . With the move to new premises and the entrance of the administration as a new actor, the power relations in a historical set between the different participants were modified , because not only had to build this new social space , but involved a series parallel of adjustments in practices , representations and interaction styles traditionally rooted . These changes resulted in a series of tensions that arise from the way it was designed and how the company has been administered , and that evidence of gains and losses background who lived each one of the agents there immersed in a constant battle space and confrontation as is the market. Thus, from a conceptual perspective to understand the market , analyze the changes inside, drawing parallels between the situation described the market who qualify as a colonial institution , and it is now possible to identify from the information collected in fieldwork . It is then to show that what happened in this social space is indeed accurate and cyclical events such as the creation of the wholesaler , but also respond to changes in society in general, and their transformations in the economic and social sectors of the inhabitants of surrounding neighborhoods .